Identification of network externalities in markets for non-durables - Michal Grajek (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
This paper introduces a structural econometric model of consumer demand for nondurable goods, which exhibits network externalities. The structural model allows us to identify the parameters, which determine the strength of the externalities in the underlying economic model from the empirical estimation results. The estimates of these parameters can then be employed to test the economic significance of the externalities and the compatibility of networks. The identifying assumption that drives our results is that consumers care about the lagged instead of the current network size. We argue that it does not necessarily bound their rationality. To complete our structural model, we provide an example of functional specification that yields a simple linear stochastic model of demand. Using this functional specification, we identify all structural parameters of the model. In the end, the estimation and the stochastic structure of the resulting econometric model are discussed. – – Der vorliegende Beitrag stellt ein strukturelles ökonometrisches Modell der Konsumnachfrage für nicht-dauerhafte Güter mit externen Netzwerkeffekten vor. Das strukturelle Modell lässt uns die Parameter von Netzwerkeffekten im zugrunde liegenden ökonomischen Modell empirisch zu identifizieren. Die Schätzer der Strukturparameter könnten für das Testen der Netzwerkkompatibilität und der ökonomischen Signifikanz der Netzwerkeffekte verwendet werden. Für die Identifikation nehmen wir an, dass die Konsumenten die Netzwerksgröße verzögert wahrnehmen. Wir argumentieren, dass diese Annahme nicht notwendigerweise mit irrationalem Verhalten gleichzusetzen ist. Um das strukturelle Modell zu vollständigen, geben wir eine funktionale Spezifikation, aus der ein lineares stochastisches Nachfragemodell folgt. Unter Verwendung dieser Spezifikation sind alle Strukturparameter von dem Modell identifiziert. Zum Schluss diskutieren wir die Schätzung und die stochastische Struktur des sich ergebenden ökonometrischen Modells.
Keywords: C51; D12; 330; Structural Econometric Model; Network Externalities; Innovation Diffusion